2017
DOI: 10.1186/s13601-017-0179-2
|View full text |Cite
|
Sign up to set email alerts
|

Is a positive intracutaneous test induced by penicillin mediated by histamine? A cutaneous microdialysis study in penicillin-allergic patients

Abstract: BackgroundDiagnostic workup of penicillin allergy comprises skin testing with penicillins, and patients are deemed allergic if skin test is positive. However, the literature suggests that skin test-positive patients may be challenge-negative, indicating that the skin test may be falsely positive.ObjectiveTo investigate real-time histamine release from a positive intracutaneous test induced by penicillin in patients with positive and negative challenges to penicillin.MethodsSkin microdialysis was performed in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Among patients reporting nonimmediate reactions (largely maculopapular exanthema or urticaria/angioedema), 26,28,32,40,42,46 Eleven studies were included in the meta-analysis assessing the accuracy of specific IgE. 24,28,30,33,[36][37][38][39]42,47,48 The studies had been mostly performed in Europe (n 5 10), 24,28,30,33,36,38,39,42,47,48 and among outpatients (n 5 9). 24,28,33,[36][37][38][39]42,47,48 Four studies assessed adults, 28,37,38,47 whereas 3 assessed children 36,42,48 and other 4 studies patients of all age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Among patients reporting nonimmediate reactions (largely maculopapular exanthema or urticaria/angioedema), 26,28,32,40,42,46 Eleven studies were included in the meta-analysis assessing the accuracy of specific IgE. 24,28,30,33,[36][37][38][39]42,47,48 The studies had been mostly performed in Europe (n 5 10), 24,28,30,33,36,38,39,42,47,48 and among outpatients (n 5 9). 24,28,33,[36][37][38][39]42,47,48 Four studies assessed adults, 28,37,38,47 whereas 3 assessed children 36,42,48 and other 4 studies patients of all age groups.…”
Section: Resultsmentioning
confidence: 99%
“…Penicillins can directly activate the RhoA/Rock signaling pathway, which affects endothelial hyperpermeability. 39 Tannert and coworkers 40 recently reported that histamine was only detected in a few positive intracutaneous penicillin skin test results by microdialysis.…”
Section: Optimal Penicillin Allergy Testing Protocols Based On Reactimentioning
confidence: 99%
“…So far, SMD has been used to a limited extent in the investigation of drug hypersensitivity. In one study, SMD in penicillin allergic patients demonstrated that histamine was only released in the minority of positive intracutaneous tests with penicillin [38 ].…”
Section: How Smd Has Helped Us To Understand Skin Inflammation and Skmentioning
confidence: 99%